PHP Oracle web development : data processing, security, caching, XML, web services and AJAX : a practical guide to combining the power, performance, scalability, and reliability of Oracle Database with the ease of use, short development time, and high performance of PHP /: data processing, security, caching, XML, web services and AJAX : a practical guide to combining the power, performance, scalability, and reliability of Oracle Database with the ease of use, short development time, and high performance of PHP. (©2007) - Unknown
No abstract available